Elucidation of photodegradation of p-chlorophenol in a biophotoelectric reductive degradation system by density functional theory calculations. (July 2020) - Liu, Peng-Cheng; Ma, Xiao-Lin; Li, Ting-Ting; Yan, Feng; Wu, Li-Jun; Xiao, Xiang
Abstract: Anaerobic photocatalysis of semiconductors is a promising approach for the remediation of refractory pollutants which are readily reduced rather than oxidized. To sustain the operation of photoreduction, hole scavengers must be supplied. Bacteria as hole scavengers have attracted great attention. Thus, a bio-photoelectric reductive degradation system (BPRDS) was established by integrating nano-Ag3 PO4 and Shewanella oneidensis MR-1. Photodegradation performance of BPRDS was evaluated via degrading p -chlorophenol ( p -CP). Results showed that p -CP could be degraded by BPRDS under anaerobic photoexcitation conditions, but not be decomposed by Shewanella cells or nano-Ag3 PO4 . Block of extracellular electron transfer of S. oneidensis MR-1 could reduce p -CP degradation in BPRDS, implying bio-electrons were involved in anaerobic photodegradation process. Dose of riboflavin decreased the photodegradation efficiency significantly. DFT calculations revealed that bio-electrons released by S. oneidensis MR-1 could be transferred to photogenerated holes of nano-Ag3 PO4 to exert biological hole scavengers. Hole and hydroxyl radical scavengers could not prevent degradation of p -CP in BPRDS, implying p -CP was removed via photoreduction rather than photooxidation. Our results demonstrate that EAB can act as biological hole scavengers for anaerobic photodegradation of pollutants, which will contribute to the application of BPRDS for environmental remediation. Highlights: A BPRDS was constructed by integrating S. oneidensis MR-1 and nano-Ag3 PO4 . p -chlorophenol ( p -CP) was degraded in BPRDS under anaerobic photoexcitation. Electrons produced by Shewanella drove the BPRDS operation. DFT calculations determined Shewanella as biological hole scavenger in BPRDS.